Designing liquid-crystalline gold nanoparticles via the olefin cross-metathesis reaction - Nguyen, Thanh Tung; Nguyen, Thi Le Anh; Deschenaux, Robert (My University, 2016)
Liquid-crystalline gold nanoparticles were prepared by grafting mesomorphic α,β- unsaturated carbonyl olefins onto the organic shell of gold nanoparticles containing terminal olefin ligands by applying the olefin cross-metathesis. The latter reaction was performed under standard conditions using second-generation Grubbs catalyst. The title materials were found to be stable up to 200 °C and gave rise to the formation of smectic A phases in agreement with the structure and nature of the liquid-crystalline promoters. The olefin cross-metathesis proved to be a reaction of choice for the design of liquid-crystalline nanoparticles.
Keywords: olefin cross-metathesis; liquid crystals; gold nanoparticles